2015
DOI: 10.1155/2015/685613
|View full text |Cite
|
Sign up to set email alerts
|

Mental State Inferences Abilities Contribution to Verbal Irony Comprehension in Older Adults with Mild Cognitive Impairment

Abstract: Objective. The present study examined mentalizing capacities as well as the relative implication of mentalizing in the comprehension of ironic and sincere assertions among 30 older adults with mild cognitive impairment (MCI) and 30 healthy control (HC) subjects. Method. Subjects were administered a task evaluating mentalizing by means of short stories. A verbal irony comprehension task, in which participants had to identify ironic or sincere statements within short stories, was also administered; the design of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 44 publications
1
20
0
2
Order By: Relevance
“…Seventeen studies involving 513 (55.6% females) individuals with MCI and 693 (60.5% females) healthy controls were included (Table 1). 1112,14,19–20,21 32 Fourteen of these studies used Petersen criteria and other 3 used IWG criteria to define MCI. Thirteen of 17 studies included only aMCI and other 2 studies reported task performances of separate aMCI and naMCI groups.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Seventeen studies involving 513 (55.6% females) individuals with MCI and 693 (60.5% females) healthy controls were included (Table 1). 1112,14,19–20,21 32 Fourteen of these studies used Petersen criteria and other 3 used IWG criteria to define MCI. Thirteen of 17 studies included only aMCI and other 2 studies reported task performances of separate aMCI and naMCI groups.…”
Section: Resultsmentioning
confidence: 99%
“…However, in 2 studies that distinguished first- and second-order false belief tasks, MCI was associated with impairment only in second-order tasks. 21,23 Most individuals with MCI might fail only in cognitively more demanding ToM tasks due to deficits in nonsocial cognitive abilities such as executive dysfunction. In accordance with this notion, mild prefrontal neurodegeneration is evident in many patients with aMCI.…”
Section: Discussionmentioning
confidence: 99%
“…The ability to draw inference was also impaired in our aMCI group and the performance was similar to that of the AD group. In a recent study, Gaudreau [49] showed that aMCI individuals were impaired in their mental inference capacity when compared to Controls. The aMCI group presented more difficulties to identify ironic or sincere stories.…”
Section: Discussionmentioning
confidence: 99%
“…This decline in cognitive functioning was first detected through participants’ complaints, which in turn were confirmed by a close relative. To confirm the presence of MCI, procedures similar to those adopted by Gaudreau et al (2015) were followed. Briefly, the MCI was confirmed based on a battery of clinical and neuropsychological tests that was administered.…”
Section: Methodsmentioning
confidence: 99%